Economic analysis of the link between diet quality and health: Evidence from Kosovo - Braha, Kushtrim; Cupák, Andrej; Pokrivčák, Ján; Qineti, Artan; Rizov, Marian (Economics and human biology, 2017)
We analyse the link between diet diversity, (which is a proxy of diet quality) and health outcomes measured by body-mass index (BMI) in a representative sample of Kosovar adults using household expenditure micro-data. Building on a household model of health production we devise a two-stage empirical strategy to estimate the determinants of diet diversity and its effect on BMI. Economic factors and demographic characteristics play an important role in the choice of balanced diets. Results from the BMI analysis support the hypothesis that diet diversity is associated with optimal BMI. One standard deviation increase in diet diversity leads to 2.3% increase in BMI of the underweight individuals and to 1.5% reduction in BMI of the obese individuals. The findings have important implications for food security policies aiming at enhancing the public health in Kosovo.
Keywords: dospělí; Female; Adult; ženské pohlaví; mladý dospělý; Adolescent; Obesity; hubenost; Health Status; Models, Econometric; lidé; zdravotní stav; Thinness; Kosovo; ekonometrické modely; Aged, 80 and over; dieta; obezita; Diet; Male; Aged; Socioeconomic Factors; Young Adult; index tělesné hmotnosti; lidé středního věku; senioři nad 80 let; socioekonomické faktory; senioři; mužské pohlaví; Body Mass Index; Middle Aged; mladiství; Humans